Crisis and Correspondence Style in the Nineteenth Century - Hvattum, Mari 1966- (2013)
In his manifesto Das Kunstwerk der Zukunft (1850), Richard Wagner characterised the nineteenth century as a time of crisis. Echoing Saint-Simon, he defined this crisis as a discrepancy between the spirit of the age and the actual, historical conditions. Evoking some of the most potent concepts of modern thinking—Zeitgeist, genius, and the Gesamtkunstwerk—Wagner outlined an aesthetic theory by which the artwork (including architecture) simultaneously reflects and shapes its context, serving both as a mirror of its age and an agent of change. Wagner’s seemingly paradoxical notion of art provides an apt introduction to historicist thinking. Obsessed with the idea of correspondence (or the lack of it) between art and its times, nineteenth-century thinkers such as Heinrich Hübsch, Carl Bötticher and Gottfried Semper all responded to the perceived crisis. While Hübsch and Bötticher sought to alleviate the crisis by redefining this correspondence for a modern world, Semper presented a far more radical alternative. Not only did he see the current crisis as inevitable; he welcomed it as a necessary dissolution of an old order, out of which a new architecture could emerge. He thus anticipated modernists, such as Sigfried Giedion, for whom historicism was a necessary melt-down; an apocalypse, preparing for the advent of modernism. In this essay, I propose that crisis and style are intrinsically linked in modern thinking. To look closely at this coupling may throw new light not only on historicism but also on the noticeable unease with which the notion of style is treated in contemporary architectural history.
Keywords: Crisis, style, Richard Wagner, Gottfried Semper, Heinrich Hübsch, Carl Bötticher